A Novel Perspective on the Proactive and Reactive Controls of Executive Function in Chronic Stroke Patients - Yu, Qiuhua; Huang, Xiaomin; Zhang, Baofeng; Li, Zhicheng; Zhang, Tao; Hu, Ziwei; Ding, Minghui; Liang, Zhenwen; Lo, Wai Leung Ambrose (Frontiers in Neurology, 2022)
Objectives: To investigate the proactive and reactive control process when executing a complex task in patients with stroke. Proactive control is the preparatory process before the target stimulus, whereas reactive control is an imperative resolution of interference after the target stimulus. Methods: Seventeen patients with chronic stroke and seventeen healthy individuals were recruited. The proactive and reactive control of executive function was assessed by the task-switching paradigm and the AX version of the Continuous Performance Task (AX-CPT). The general executive function was assessed by Color Trial Test (CTT) and Stroop Test. The behavioral data of the task-switching paradigm were analyzed by a three-way repeated-measures ANOVA, and the AX-CPT data were analyzed by two-way repeated-measures ANOVA. Results: For efficiency scores in the task switching paradigm, trial (repeat vs. switch)×group (stroke or control group) interaction effect was significant. Post hoc analysis on trial×group effect showed significant between-trial difference in accuracy rates in the repeat trial in the control group regardless of 100% or 50% validity. For the AX-CPT, the main effects of condition and group on response time were statistically significant. The interaction effect of condition (AY or BX)×group (stroke or control group) was also significant. Post hoc analysis for condition×group indicated that the stroke groups had a significantly longer response time in the BX condition than the control group, and longer completion time in CTT2 and larger word interference for completion time in Stroop test than the control cohort. Conclusions: Post-stroke survivors showed deficits in the performance of proactive control but not in the performance of reactive control. Deficits in proactive control may be related to impairment of working memory. Interventions that focus on proactive control may result in improved clinical outcome.